Task performance: effects of motivation and sex (2000)
The objective of this study was to investigate if students would perform better on creativity testing when exposed to extrinsic motivation, or when exposed to intrinsic motivation, and also to determine whether there was sex difference in task performance. Eighty subjects, 40 males and 40 females (senior secondary students) were randomly selected. Forty (40) of the subjects were exposed 10 extrinsic motivation (monetary reward) while the other forty (40) were not given any reward the intrinsic motivation group. Creativity Testing Scale was administered to subjects in each group, A 2 x 2 Analysis of Variance (ANOVA) was used to determine the effects of motivation and sex on Task Performance. The findings showed that the subjects exposed to extrinsic motivation performed better than those exposed to intrinsic motivation. It was also found that there was no significant sex difference in performance. The implication of this is that when people are given tangible rewards their performance would be enhanced, also males as well as females can both perform equally on creativity.